2022
DOI: 10.1021/acsphyschemau.2c00003
|View full text |Cite
|
Sign up to set email alerts
|

Computational Insight into TM–Nx Embedded Graphene Bifunctional Electrocatalysts for Oxygen Evolution and Reduction Reactions

Abstract: Due to the energy crisis, development of bifunctional electrocatalysts for both oxygen evolution and reduction reactions is highly demanding. In this study, we have systematically investigated the bifunctional activity of metal (Co/Rh/Ir) and N co-doped graphene systems with varying N-dopant concentrations (TM−N x @G, x = 0, 2, 4) using first-principles calculations. Charge transfer from the metal sites to the adsorbed intermediates and the adsorption free energy of the intermediates play important roles to he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…One of the criticisms outlined in the Section refers to the fact that the four-electron ORR in volcano plots is often entirely described by the mononuclear mechanism (cf. eqs 3–6), albeit different mechanistic pathways have been put forth in the literature. While it has been suggested that gaseous oxygen can adsorb in a dissociative fashion on the catalyst surface, the formation of two adjacent *O adsorbates is not promoting the formation of H 2 O 2 , and thus, it is corroborated to focus on mechanistic descriptions comprising the *OOH adsorbate. In this context, it was reported that the *OOH adsorbate can alternatively dissociate in a chemical or an electrochemical step to form *O and *OH or *OH and *OH, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the criticisms outlined in the Section refers to the fact that the four-electron ORR in volcano plots is often entirely described by the mononuclear mechanism (cf. eqs 3–6), albeit different mechanistic pathways have been put forth in the literature. While it has been suggested that gaseous oxygen can adsorb in a dissociative fashion on the catalyst surface, the formation of two adjacent *O adsorbates is not promoting the formation of H 2 O 2 , and thus, it is corroborated to focus on mechanistic descriptions comprising the *OOH adsorbate. In this context, it was reported that the *OOH adsorbate can alternatively dissociate in a chemical or an electrochemical step to form *O and *OH or *OH and *OH, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…eqs 3–6). Even if the presence of the *OOH intermediate is well accepted, several other mechanistic pathways have been suggested in the literature, and these mechanisms are commonly not included in the volcano analysis. Consequently, if the mononuclear mechanism does not correspond to the energetically favored pathway, the electrocatalytic activity of the four-electron ORR may be underestimated, and thus, trends in a class of materials are not correctly assessed when using the concept of volcano curves The concept of the limiting potential for approximation of electrocatalytic activity relies on thermodynamic considerations at the equilibrium potential of the ORR, and correspondingly, does not capture overpotential and kinetic effects in the analysis of binding energies .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The onset of this study is a consistent set of hydrogen chemisorption energies. These were obtained theoretically from density functional theory (DFT) calculations and, all calculations employed the TPSSh meta-generalized- gradient-approximation exchange–correlation functional in calculating transition states and energy barriers 45 . The dipole correction was applied throughout the calculation to take into account the polarization effects of the studied surfaces 46 – 49 .…”
Section: Resultsmentioning
confidence: 99%
“… ΔGnormalpnormalH ${{\rm \Delta }{{\rm G}}_{{\rm p}{\rm H}}}$ is the correction of the H + free energy, which can be expressed as ΔGnormalpnormalH=kBT×pH×ln10 ${{\rm \Delta }{{\rm G}}_{{\rm p}{\rm H}}={{\rm k}}_{{\rm B}}T\times pH\times ln10}$ , where normalknormalB ${{{\rm k}}_{{\rm B}}}$ is the Boltzmann constant. The value of pH is assumed to be zero in this work for simplicity [63] . The zero‐point energy (ZPE) and entropies of the reaction intermediates are computed form the vibrational frequencies and the Boltzmann distribution [64] is employed as equation (3) and . EZPE=12ihνiand, $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr {{\rm \ }E}_{ZPE}={{1}\over{2}}\sum _{i}h{\nu }_{i}\ {\rm and}{\rm \char44 }\ \hfill\cr}}$ -TS=KBTiln1-e-hνiKBT-ihνi1ehνiKBT-1 $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr -TS={K}_{B}T\sum _{i}ln\left(1-{e}^{-{{h{\nu }_{i}}\over{{K}_{B}T}}}\right)-\sum _{i}h{\nu }_{i}\left({{1}\over{{e}^{{{h{\nu }_{i}}\over{{K}_{B}T}}}-1}}\right)\ \hfill\cr}}$ …”
Section: Methodsmentioning
confidence: 99%